Understanding Conceptualizations of Pregnancy and Planning for Pregnancy Among Adolescent Girls and Young Women in Harare, Zimbabwe. (July 2018) - Tinago, Chiwoneso B.; Ingram, Lucy Annang; Frongillo, Edward A.; Blake, Christine E.; Engelsmann, Barbara; Simmons, David
Zimbabwe has one of the highest rates of maternal mortality, yet little is understood about adolescent girls' and young women's perspectives on pregnancy or planning for pregnancy. The research study took an emic approach to understand and describe how adolescent girls and young women (14–24 years) in Harare, Zimbabwe, conceptualize pregnancy and planning for pregnancy and how these conceptualizations inform pregnancy decisions. Semi-structured, in-depth, qualitative interviews were conducted with adolescent girls and young women ( N = 48) and data were analyzed thematically using NVivo 10. Pregnancy was conceptualized across nine themes: carrying a child and oneself, growing a family, motherhood, the best time for pregnancy, pregnancy decision makers, who is responsible for the pregnancy, pregnancy burden, pregnancy dangers, and increase in social status with pregnancy. Planning for pregnancy was conceptualized during the prepregnancy, pregnancy, and postpregnancy phases. Findings emphasize considering sociocultural views concerning pregnancy and including social networks in maternal health efforts.